2019
DOI: 10.7759/cureus.5363
|View full text |Cite
|
Sign up to set email alerts
|

Reflex Sympathetic Dystrophy of the Right Hand following an Acute Traumatic Injury

Abstract: Complex regional pain syndrome (CRPS), formerly known as reflex sympathetic dystrophy, is a chronic neuropathic pain disorder with significant autonomic features. Recently, it has been recognized that CRPS is not simply a sympathetically mediated peripheral pain condition but rather a disease of the central nervous system as well. Herein, we present a case of a patient who presented with complaints of severe pain following a traumatic event, severing his extensor tendon of his right fifth finger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…The duration of pain relief after PRF of stellate ganglion in our case was one week. Previous studies have reported that a brachial plexus block as a single block or continuous infusion through a catheter inserted with local anesthesia and an additive such as steroids or morphine can treat the pain of CRPS patients 18 . Wong and Wilson reported pain relief with a brachial plexus catheter using the axillary approach in a patient with severe CRPS 19 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The duration of pain relief after PRF of stellate ganglion in our case was one week. Previous studies have reported that a brachial plexus block as a single block or continuous infusion through a catheter inserted with local anesthesia and an additive such as steroids or morphine can treat the pain of CRPS patients 18 . Wong and Wilson reported pain relief with a brachial plexus catheter using the axillary approach in a patient with severe CRPS 19 .…”
Section: Discussionmentioning
confidence: 99%
“…19 An interscalene block was evaluated and reported to be as effective as SGB for the management of severe pain in a patient with CRPS. 18 Kingery used an interscalene block with an infusion pump of bupivacaine for a period of 3 to 6 months and showed good results in patients with CRPS. 20 Fallatah reported the successful management of CRPS type 1 using a single interscalene brachial plexus block and showed dramatic improvement after one injection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations